Efektivitas Pelatihan Berpikir Positif untuk Menurunkan Kecemasan Mengerjakan Skripsi pada Mahasiswa - Atina Machmudati; R. Rachmy Diana (Universitas Islam Indonesia, 2017)
This research aims to know the effectiveness of positive thinking training in reducing the anxieties of students who are working on the thesis. The subjects in this research consisted of 24 students which 12 students into experimental group and 12 students into the control group. The subjects characteristics of the research is : 1) students of UIN Sunan Kalijga especially students of Social anda Humanities Faculty and Science and Technology Faculty 2) doing thesis, 3) having medium up to highest anxiety score in doing thesis, 4) ready to be subject of the research.This research uses two deferent groups (experimental and control groups) by pre-test and post-test design. The measurenment tool which is use in the research is the anxiety doing the thesis scale.The test using statistical analysis techniques Mann Whitney U indicates that gain score between control and experimental group results value p=0,002 (p<0,005) so it can be concluded that there is a difference score of anxiety that significant between experimental and control group. Whereas the analysisresults of wilcoxon signed rank indicates that post-test and pre-test experimental group gets value p=0,002 (p<0,005), so it can be concluded that there is different of anxiety level on experimental group before and after treatment. The anxiety of students after getting positive thinking treatment indicates lower than before.Keywords: Positive thinking training, anxiety, students.